ANALISIS KEPUASAN KONSUMEN TERHADAP BRAND SWITCHING BEHAVIOR MINUMAN TEH DALAM KEMASAN - Susila, Budi; Sumarwan, Ujang; Kirbrandoko, Kirbrandoko (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2014)
The objective of the study is to analyze the customer switching behavior of the ready to drink (RTD) tea. Switching behavior is a form of customer loyalty that reflects on proportion of purchase in certain period of time. This study aims to analyze the influence of marketing mix dimension on customer satisfaction and switching behavior. Data was collected by survey method and personal interview using questionnaire. The sample was selected by quota sampling method (n=154, 40 percent from Jakarta, 20 percent from Bogor, 20 percent from Tangerang, and 20 percent from Bekasi). The variables of this research were marketing mix dimension, consisted of five aspects are product’s quality, price, availability, products’ communication, and brand reputation. The marketing mix dimensions were analyzed by descriptive analysis methods and Structural Equation Model (SEM) to examine its associate with satisfaction and switching behavior. The result showed that products’ quality and brand reputation significantly associated with customer satisfaction. Switching behavior of ready to drink (RTD) tea conducted by consumer when there was no availibility of the desired brands.